Taxonomía de algunos microtéidos (Squamata) de Venezuela, I: Variación y distribución geográfica de Euspondylus acutirostris y descripción de un nuevo Euspondylus del nordeste de Venezuela - Mijares-Urrutia, Abraham; Celsa Señaris, J; Arends, Alexis (Revista de Biología Tropical, 2000)
Only two species of the microteiid lizard genus Euspondylus (E. acutirostris and E. phelpsorum) had been reported from Venezuela. New records of the poorly known gymnophthalmid lizard Euspondylus acutirostris are reported extending its known range along the Coastal Range and Sierra de Aroa (north-central Venezuela) and Sierra de San Luis (northwestern Venezuela), aH record s occurring at the cloud forest aboye 1000 m. Seven body measurements were included and morphological variation is described based on at least 17 new specimens. Sexual dimorphism is determined in, at least, eight characteristics of size and squamation. Specimens were found in epiphytic bromeliads and the ground. The populations from Sierra de Aroa and Sierra de San Luis (only one specimen known from each locality), differ from those of the Coastal Range (supposedly the nominal population) in sorne morphological and coloration features, suggesting that th ! former two could represent different taxonomical entities. A new species of Euspondylus is described based on a female (taken within a bromeliad) from Cerro El Humo, Sucre, northeastern Venezuela. It differs from congeners mainly by having keeled scales on the limbs and a very acute snout.